2002
DOI: 10.1093/jn/132.6.1165
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Inhibits Microsomal Triglyceride Transfer Protein Gene Expression in Human Liver and Intestinal Cell Lines and in Rat Intestine

Abstract: Epidemiologic studies have suggested that fresh garlic has lipid-lowering activity. Because the microsomal triglyceride transfer protein (MTP) plays a pivotal role in the assembly and secretion of apolipoprotein B (apoB)-containing lipoproteins, we evaluated the effect of garlic on the expression of the MTP gene in vitro in cell lines and in vivo in rats. Fresh garlic extract (FGE) reduced MTP mRNA levels in both the human hepatoma HepG2 and intestinal carcinoma Caco-2 cells in dose-dependent fashion; signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…42 Various garlic extracts have been shown to decrease the activities of NADPH-producing enzymes and of fatty acid synthetase in vitro and in vivo. 17,18,43 It has also been postulated that the plasma TG lowering effect may also be, in part, due to decreases in intestinal microsomal TG transfer protein mRNA 44 and apolipoprotein B100 secretion. 14 Over-production of apolipoprotein B100 containing lipoproteins can lead to atherosclerosis and coronary heart disease and also induces hyperlipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…42 Various garlic extracts have been shown to decrease the activities of NADPH-producing enzymes and of fatty acid synthetase in vitro and in vivo. 17,18,43 It has also been postulated that the plasma TG lowering effect may also be, in part, due to decreases in intestinal microsomal TG transfer protein mRNA 44 and apolipoprotein B100 secretion. 14 Over-production of apolipoprotein B100 containing lipoproteins can lead to atherosclerosis and coronary heart disease and also induces hyperlipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is an edible wild plant that belongs to family Portulaceae. The leaves of purslane are commonly used as food staff, since they contain high ratio of ascorbic acid [162]. Purslane extract in the form of ethanolic formulation is rich in polyphenols, flavonoids and anthocyanin, ω-3 fatty acids, and melatonin.…”
Section: Purslanementioning
confidence: 99%
“…Saponin fractions from garlic lowered plasma total and LDL cholesterol concentrations without changing HDL cholesterol levels in a hypercholesterolaemic animal model (Matsuura 2001 ). In-vivo studies in rats suggested that long-term dietary supplementation of fresh garlic may exert a lipid-lowering effect partly through reducing intestinal MTP mRNA gene expression, thus, suppressing the assembly and secretion of chylomicrons from the intestine to the blood circulation (Lin et al 2002 ). In-vitro, fresh garlic extract reduced MTP mRNA levels in both the human hepatoma HepG2 and intestinal carcinoma Caco-2 cells in a dosedependent fashion.…”
Section: Animal Studiesmentioning
confidence: 99%